Dural puncture epidural analgesia for labor: a randomized comparison between 25-gauge and 27-gauge pencil point spinal needles. Issue 7 (22nd May 2019) - Contreras, Felipe; Morales, Juan; Bravo, Daniela; Layera, Sebastián; Jara, Álvaro; Riaño, Carlos; Pizarro, Rodrigo; De La Fuente, Natalia; Aliste, Julián; Finlayson, Roderick J; Tran, De Q
Abstract : Background: This double-blind, randomized trial compared dural puncture epidural analgesia (DPEA) for labor using 25-gauge and 27-gauge pencil point spinal needles. We hypothesized that both needle sizes would result in similar onset time (equivalence margin=2.5 min) and therefore designed the study as an equivalence trial. Methods: One hundred and forty patients undergoing labor were randomized to DPEA with 25-gauge (n=70) or 27-gauge (n=70) pencil point spinal needles. After the placement of the epidural catheter, a bolus of 20 mL of bupivacaine 0.125% and fentanyl 2 µg/mL was administered to all subjects. Thereafter, patients received boluses of 12 mL of bupivacaine 0.125% every 2 hours as needed. A blinded investigator recorded the onset time (defined as the temporal interval required to achieve a pain score ≤1 on a 0–10 scale), S2 block, sensory block height (30 min after the initial bolus of local anesthetic), presence of motor block (30 min after the initial bolus of local anesthetic), number of top-up doses required during labor and incidence of postural headache. Results: Out of the 140 recruited patients, 135 were retained for analysis. Compared with their 27-gauge counterparts, 25-gauge pencil point spinal needles provided a 1.6 min shorter DPEA onset (95% CI of the difference of the means: −3.2 to −0.1 min). However, there were no intergroup differences in terms of S2 block, sensory block height, motor block, number of top-up doses and incidence of postural headache. Conclusion: Dural puncture epidural analgesia with 25-gauge pencil point spinal needles provides a 1.6 min shorter onset time than DPEA with 27-gauge spinal needles. Although statistically significant, such a difference may not be clinically relevant. Further investigation is required to compare 25-gauge and 27-gauge spinal needles for DPEA in the setting of different local anesthetic infusion strategies. Trial registration number: NCT03389945 .